2020
DOI: 10.21203/rs.3.rs-48737/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Anosmia and Ageusia in Patients with COVID-19 at a Primary Health Center, Doha, Qatar

Abstract: Background: Loss of smell and taste are common complaints in patients with the COVID-19 disease. These symptoms may present alone or with other symptoms. It is of utmost importance to know their rates of occurrence for better controlling of the infection. Objectives: To detect the prevalence of anosmia and ageusia in individuals with COVID-19 in Al-Wajbah Primary Health Center, Doha, Qatar.Materials and methods: This retrospective study was conducted at Al-Wajbah Primary Health Center, Doha, Qatar. The study c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
3
11
1
Order By: Relevance
“…As per Lechien et al, they reported up to 85.6% COVID-19 patients with olfactory dysfunction and 88% patients had gustatory dysfunctions [ 6 ]. Similar results of 68% and 71% regarding prevalence of smell and taste disorder has been found in COVID-19 patients in a study from USA, [ 36 ] whereas, low prevalence rates (5.1 to 24.8% for OD; 5.6 to 20.6% for GD) are mentioned in studies from Asian region [ 5 , 31 , 32 , 37 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As per Lechien et al, they reported up to 85.6% COVID-19 patients with olfactory dysfunction and 88% patients had gustatory dysfunctions [ 6 ]. Similar results of 68% and 71% regarding prevalence of smell and taste disorder has been found in COVID-19 patients in a study from USA, [ 36 ] whereas, low prevalence rates (5.1 to 24.8% for OD; 5.6 to 20.6% for GD) are mentioned in studies from Asian region [ 5 , 31 , 32 , 37 ].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, to accrue the data we relied on a questionnaire which was filled by the patient online or by telephonic interview from proven COVID-19 patients. Various other studies have also relied on such methodology [6,[30][31][32]. While others have relied on objective testing, performed by the health worker or self-administered after explaining the procedure [9,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found significant associations between self-reported olfactory disorders and female gender [ 2 , 7 , 32 , 33 , 34 , 35 ], younger age [ 32 , 33 , 36 , 37 , 38 ], smoker [ 39 ] or no-smoker [ 33 ] habit, hypertension [ 15 ], diabetes [ 18 ], depression [ 40 ], or symptoms such as fever [ 2 ] and nasal obstruction [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the symptoms, although the median onset (IQR) was 0 day (0-2.5), more than one third of the participants (n=104, 34.3%) presented symptoms at the enrolment day. The more common symptoms at presentation were fever (n=39, 12.9%), myalgia (n=31, 10.3%) and headache (n=24, 7.9%), corresponding to flu symptoms, followed by cough (n=21, 6.9%) and anosmia/ageusia (n=20, 6.6%) which were frequently reported in Covid-19 clinical diagnosis criteria [28,29].…”
Section: Resultsmentioning
confidence: 99%